Quality standards, value chains, and international development : economic and political theory - Swinnen, Johan F. M.; Deconinck, Koen; Vandemoortele, Thijs; Vandeplas, Anneleen (Cambridge University Printing House, 2015)
This book offers the first theoretical analysis of the determination of quality standards and their effects along the value chain.
Includes bibliographical references and index.
osa 24/10/17
Loans
Keywords: Value; International trade; Economic development